Mining Public Metagenomes for Environmental Surveillance of Parasites: A Proof of Principle - Franssen, Frits F. J.; Janse, Ingmar; Janssen, Dennis; Caccio, Simone M.; Vatta, Paolo; van der Giessen, Joke W. B.; van Passel, Mark W. J. (Frontiers in Microbiology, 2021)
Abstract Parasites often have complex developmental cycles and can be present in a variety of difficult-to-analyze matrices, including feces, water, soil and food, in which detection still involves laborious methods. Untargeted sequencing of nucleic acids extracted from those matrices may represent an attractive alternative method for unbiased detection of these pathogens. Here, we show how publicly available metagenomic datasets can be mined to detect parasite specific sequences, and generate data useful for environmental surveillance. We show how the detection of the protozoan parasite Cryptosporidium parvum is impacted by the choice of the reference sequence used. In particular, we show that the use of the whole genome yields high sensitivity but low specificity, and that specificity can be improved through the use of signature signatures. In conclusion, querying metagenomics datasets for parasites is feasible and relevant, but requires optimization and validation. Nevertheless, this approach provides access to the large, and rapidly increasing, number of datasets from metagenomics and meta-transcriptomic studies. Dedicated metagenomics projects of relevant matrices will be instrumental to define the detection limit and the possibility of a reliable identification of parasites at the species/genotype level.